The stress and flexibility analysis of thin-walled curved pipes under out-of-plane bending with the semi-membrane ring element - Melo, F. J. M. Q. de (1990)
A semi-membrane curved ring element, described in a previous paper, is reformulated to take into account more general loading conditions, such as the out-of-plane bending. A new displacement field was defined so that the out-of-plane bending moment could be considered. Results concerning transverse section stresses and flexibility factors are presented and discussed.